Dialectical hermeneutics: an experience as a method of analysis in research on the user access to pharmaceutical services - Tatiane de Oliveira Silva Alencar; Maria Angela Alves do Nascimento; Bruno Rodrigues Alencar (Universidade de Fortaleza, 2012)
Objective: To describe the application of dialectical hermeneutics as a method of analysis in research on pharmaceutical services. Data Synthesis: This is the description of a qualitative approach method of analysis, used in a research having as its object of study the user access to the Pharmaceutical Services and its analysis based on understanding of the dimensions of access (geographical, economic, functional, availability and communicational) defined by various experts in the area. There is delimitation of subjects and criteria applied for their inclusion, techniques (systematic observation, semi-structured interviews and analysis of documents) and instruments for data collection, and the steps involved in organizing and analyzing data according to the methodological trajectory of dialectical hermeneutics. The form of constructing the analysis tables and the analytical categories emerged from data analysis is also demonstrated. Conclusion: Detailed description of using the method of data analysis on dialectical hermeneutics basis shows its application as a methodological alternative to studies on pharmaceutical services, revealing the possibility of overcoming the usual positivist approach that characterizes them, and the possibility of its reproduction for other objects of study in public health.